2016
DOI: 10.1073/pnas.1610099113
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 causes truncation and aggregation of the Parkinson’s disease-associated protein α-synuclein

Abstract: The aggregation of α-synuclein (aSyn) leading to the formation of Lewy bodies is the defining pathological hallmark of Parkinson's disease (PD). Rare familial PD-associated mutations in aSyn render it aggregation-prone; however, PD patients carrying wild type (WT) aSyn also have aggregated aSyn in Lewy bodies. The mechanisms by which WT aSyn aggregates are unclear. Here, we report that inflammation can play a role in causing the aggregation of WT aSyn. We show that activation of the inflammasome with known sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
184
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(196 citation statements)
references
References 50 publications
8
184
1
Order By: Relevance
“…Interestingly, the inflammatory protease caspase-1 cleaves α-syn at Asp121, promoting its aggregation into amyloid fibrils similar to those previously found both in vitro and in vivo (16). In turn, the caspase-1 inhibitor prodrug VX-765 decreases α-syn truncation and aggregation in vitro and rescues cells from α-syn-induced toxicity (16). Therefore, VX-765 could exert neuroprotective effects on MSA pathogenesis by reducing α-syn cleavage, hence limiting its toxicity and its ability to form aggregates.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, the inflammatory protease caspase-1 cleaves α-syn at Asp121, promoting its aggregation into amyloid fibrils similar to those previously found both in vitro and in vivo (16). In turn, the caspase-1 inhibitor prodrug VX-765 decreases α-syn truncation and aggregation in vitro and rescues cells from α-syn-induced toxicity (16). Therefore, VX-765 could exert neuroprotective effects on MSA pathogenesis by reducing α-syn cleavage, hence limiting its toxicity and its ability to form aggregates.…”
supporting
confidence: 84%
“…Accordingly, inhibiting α-syn truncation could alter the disease course in MSA (and other synucleinopathies) (15) by decreasing α-syn oligomerization and aggregation. Interestingly, the inflammatory protease caspase-1 cleaves α-syn at Asp121, promoting its aggregation into amyloid fibrils similar to those previously found both in vitro and in vivo (16). In turn, the caspase-1 inhibitor prodrug VX-765 decreases α-syn truncation and aggregation in vitro and rescues cells from α-syn-induced toxicity (16).…”
supporting
confidence: 75%
“…However, these rodent residues are uncharged, so their role in interactions with the positively charged N terminus is less clear. Similarly, changing the negatively charged aspartic acid at position 121 to a negatively charged glutamic acid abolished caspase-1 cleavage in vitro but induced toxicity in cells (1). In addition, C-terminal αSyn interaction partners or posttranslational modifications could act as steric protectants (Fig.…”
mentioning
confidence: 98%
“…Scientists have begun identifying factors that may initiate or accelerate αSyn aggregation and how this process relates to progressive impairment of neuronal structure and function. In PNAS, companion papers by Wang et al (1) and Bassil et al (2) establish a compelling link between the accumulation of C-terminally truncated forms of αSyn created by caspase-1 and cellular dysfunction in culture and in vivo, all potentially initiated by inflammatory insults.…”
mentioning
confidence: 99%
“…α-Synuclein is a small protein (140 residues) whose mutation is associated with disease pathogenesis, and it is the main protein found in Lewy bodies of Parkinson's disease brains (16). Although the mechanism of α-synuclein-associated toxicity is still unclear, it has been shown that its disease-associated mutants are aggregation-prone and its aggregates are associated with neuronal toxicity (17,18). LRRK2 is a large (2,527 amino acids) multidomain protein whose mutation is a common cause of Parkinson's disease (19).…”
mentioning
confidence: 99%